Frailty Status Among the Elderly of Different Genders and the Death Risk: A Follow-Up Study - Shi, Jing; Tao, Yongkang; Meng, Li; Zhou, Baiyu; Duan, Chunbo; Xi, Huan; Yu, Pulin (Frontiers in Medicine, 2021)
Background: Frailty in the elderly population is currently a frontier and focus in the field of health and aging. The goal of this study was to explore the frailty status among the elderly of different genders and its influence on the risk of death during 11 years. Methods: Frailty index (FI) was used to evaluate the frailty status in the elderly based on the baseline data conducted in 2009; and death as outcome variables collected in 2020 were analyzed. The difference of the frailty level and mortality of different genders was compared. Cox regression and Kaplan-Meier curves were applied to evaluate the influence on the risk of death and the 11-year survival of the elderly at different level of frailty, respectively. Results: Totally 1246 elderly people were recruited. The mortality in men (43.7%,227/519）was statistically higher than that in women (34.3%, 249/727) （x2=11.546，P=0.001）.Deficits accumulated exponentially with age, and at all ages, women accumulated more deficits than do men on average（B=0.030 vs. B=0.028，t=4.137，P=0.023）. For any given level of frailty, the mortality rate is higher in men than in women, and the difference in mortality between genders reached the peak when FI value was 0.26. Cox regression analysis showed that FI value had a greater impact on the risk of death in older men（HR=1.171, 95%CI: 1.139～1.249）than that in older women (HR=1.119, 95%CI: 1.039～1.137). Survival analysis showed that the median 11- year survival time in women was longer than that in men (95.26 months vs. 89.52 months, Log rank=9.249, P=0.002). Kaplan-Meier curves showed that the survival rate decreased with the increase of frailty, and at the same level of frailty, survival time in older women was longer than that in older men ,except for severe frailty (FI≥0.5). Conclusion: The frailty status and its influence on mortality are different among the older people of different genders; therefore, specific interventions for frailty should be conducted in the elderly population of different genders, as well as of different degrees of frailty.